cut11(+): A Gene Required for Cell Cycle-dependent Spindle Pole Body Anchoring in the Nuclear Envelope and Bipolar Spindle Formation in Schizosaccharomyces pombe - West, Robert R. (The American Society for Cell Biology, 1998)
The “cut” mutants of Schizosaccharomyces pombe are defective in spindle formation and/or chromosome segregation, but they proceed through the cell cycle, resulting in lethality. Analysis of temperature-sensitive alleles of cut11(+) suggests that this gene is required for the formation of a functional bipolar spindle. Defective spindle structure was revealed with fluorescent probes for tubulin and DNA. Three-dimensional reconstruction of mutant spindles by serial sectioning and electron microscopy showed that the spindle pole bodies (SPBs) either failed to complete normal duplication or were free floating in the nucleoplasm. Localization of Cut11p tagged with the green fluorescent protein showed punctate nuclear envelope staining throughout the cell cycle and SPBs staining from early prophase to mid anaphase. This SPB localization correlates with the time in the cell cycle when SPBs are inserted into the nuclear envelope. Immunoelectron microscopy confirmed the localization of Cut11p to mitotic SPBs and nuclear pore complexes. Cloning and sequencing showed that cut11(+) encodes a novel protein with seven putative membrane-spanning domains and homology to the Saccharomyces cerevisiae gene NDC1. These data suggest that Cut11p associates with nuclear pore complexes and mitotic SPBs as an anchor in the nuclear envelope; this role is essential for mitosis.